The role of language games in enhancing vocabulary acquisition: A meta-analysis - A Pradheepa; K Gurusamy; T Pushpanathan (Australian Journal of Applied Linguistics)
This meta-analysis aims to investigate gamification's impact on improving second-language learners’ lexical repertoire. For this analysis 47 reviewed works are evaluated and discussed the effectiveness of gamified learning environments in the context of improving vocabulary and learning and remembering new vocabulary by the learners. This study adopted a meta-analysis review methodology for reviewing the above articles and also explores gamification methodologies, challenges and considerations, the influence of activity-specific experiences, the advancements in Digital game-based learning, the effectiveness of different strategies in gamification, and the perceptions of learners and educators towards gamified tools for learning. After a detailed analysis, the result proves that the use of gamification-enhanced vocabulary learning is better than that of conventional teaching methods. Consequently, this analysis demarcates the importance of gamification as a lively and captivating means of teaching and learning vocabulary, while making up a significant contribution to the body of knowledge in language learning.